Stepping up to the challenge - Six issues facing global climate change and food security - Deering, Karl (CARE, CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), Technical Centre for Agricultural and Rural Cooperation (CTA)., 2014)
There are several complex and interrelated challenges and barriers to achieving global food and nutrition security in an increasingly variable climate. Without urgent action for mitigation and adaptation, the world faces more loss and damage and this will further threaten the productive capacity and long-term viability of smallholder farmers.